Describing team development within a novel GP-led urgent care centre model: a qualitative study - Azeem Majeed; Geva Greenfield; Sarah Morton; Shamini Gnani; Agnieszka Igantowicz (BMJ Open)
Objective Urgent care centres (UCCs) co-located within an emergency department were developed to reduce the numbers of inappropriate emergency department admissions. Since then various UCC models have developed, including a novel general practitioner (GP)-led UCC that incorporates both GPs and emergency nurse practitioners (ENPs). Traditionally these two groups do not work alongside each other within an emergency setting. Although good teamwork is crucial to better patient outcomes, there is little within the literature about the development of a team consisting of different healthcare professionals in a novel healthcare setting. Our aim was therefore to describe staff members' perspectives of team development within the GP-led UCC model.Design Open-ended semistructured interviews, analysed using thematic content analysis.Setting GP-led urgent care centres in two academic teaching hospitals in London.Participants 15 UCC staff members including six GPs, four ENPs, two receptionists and three managers.Results Overall participants were positive about the interprofessional team that had developed and recognised that this process had taken time. Hierarchy within the UCC setting has diminished with time, although some residual hierarchical beliefs do appear to remain. Staff appreciated interdisciplinary collaboration was likely to improve patient care. Eight key facilitating factors for the team were identified: appointment of leaders, perception of fair workload, education on roles/skill sets and development of these, shared professional understanding, interdisciplinary working, ED collaboration, clinical guidelines and social interactions.Conclusions A strong interprofessional team has evolved within the GP-led UCCs over time, breaking down traditional professional divides. Future implementation of UCC models should pro-actively incorporate the eight facilitating factors identified from the outset, to enable effective teams to develop more quickly.